Prevalence of accessory septations of sphenoid sinus in pediatric population: Applications to endoscopic sinus surgery. Issue 8 (10th June 2020) - Gibelli, Daniele; Cellina, Michaela; Gibelli, Stefano; Oliva, Giancarlo; Termine, Giovanni; Dolci, Claudia; Sforza, Chiarella
Abstract: Sphenoid sinus accessory septations and their possible insertion on internal carotid artery (ICA) may represent a risk for endoscopic sinus surgical procedures. However, scarce data on this variant for children are available so far. This retrospective study included 220 maxillofacial CT‐scans equally divided among males (13.4 ± 2.1 years) and females (13.9 ± 2.2 years). On each CT‐scan, prevalence of accessory septations, number of septations in sphenoid sinuses, and their possible insertion onto ICA bone walls were recorded. Significant differences in protrusion and insertion of septations onto the ICA bone walls according to sex were assessed through Chi‐square test ( p < .05). Possible correlations between the prevalence of accessory septations, ICA insertion, and number of accessory septations and age were assessed by means of Pearson's regression ( p < .05). On average, 66% of males and 71% of females had at least one accessory septation, without significant differences according to sex or age ( p > .05): septal insertion on ICA was found in 13% of subjects, without any significant difference for sex or age ( p > .05). The number of septations was significantly increased with age ( p < .05). The present study showed that the prevalence of accessory septations and insertion onto the ICA are independent of age and these results are similar to those reported in adults. Results will be useful for the management of endoscopic sinus surgery.